Pengaruh Cyberloafing terhadap Kinerja Karyawan melalui Self Control Sebagai Variabel Moderasi pada PT Swadharma Sarana Informatika Surabaya - Hanum Sulistyowati; Dewi Nuraini (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the test results and analysis of the effect of cyberloafing on employee performance through self-control as a moderating variable at PT Swadharma Sarana Informatika Surabaya. The population and sample in this study were 86 active employees at PT Swadharma Sarana Informatika Surabaya, the sampling used was a census. The analysis method used was SPSS with Moderated Regression Analysis (MRA) analysis for testing hypothesis 3 which is a special application of multiple linear regression. The results showed that cyberloafing had a negative and significant effect on employee performance, self-control had a positive and significant effect on employee performance and self-control weakened the relationship between cyberloafing and employee performance.